Dark side of resilience: systemic unsustainability - Lyytimäki, Jari; Teperi, Anna-Maria; Jylhä, Kirsti M.; da Silva Vieira, Ricardo; Mervaala, Erkki (Frontiers in Sustainability, 2023)
Resilience is often presented as a championing solution for tackling the multi-level environmental, security, health, and financial threats facing the whole humanity or specific ecosystems, communities, institutions, or individuals. However, the popularity of the concept is not proof of its usefulness. Perhaps the greatest problem is that many of the current socio-ecological systems are operating in both resilient and unsustainable ways. The problem turns into a tragedy if resources are used to maintain or advance such unsustainable resilience. We provide a concise review of the use of the concept of resilience in multiple fields. We highlight the dominance of positive connotations of resilience, originating both from theoretical considerations and practice-oriented applications. This optimistic bias masks the fact that unsustainable systems and practices may be highly resilient. In turn, this can lead to poor understanding and inadequate management of risks related to the attempts to create sustainability innovations. We discuss how path-dependencies and shifting baselines can complicate sustainability initiatives. Managing resilience for sustainability involves defining which system states are desirable and managing the pressures that maintain desired and undesired system states. Our conclusion is that active efforts aimed for maintaining resilience should be initiated only if a thorough assessment has shown that the system under consideration can function in a sustainable way.